Pengembangan Sistem Pembelajaran Online di Masa Pandemi Covid-19 Berbasis Open Source - Alfiansyah Hasibuan; Zulfahmi Syahputra; Purwa Hasan Putra (Journal of Computer System and Informatics (JoSYC), 2020)
During the COVID-19 pandemic experienced by the world, various activities did not work as they should; one of the affected sectors was education. Education is an activity that is done face to face, but with the current conditions, forcing these activities to temporarily stopped. This research aims to develop an online learning system that is easy to understand and does not hamper the teaching and learning process in the coronavirus pandemic (Covid-19). This study uses the ADDIE model, namely, Analysis, Design, Development, Implementation, and Evaluations. Development research with the ADDIE model is limited to program implementation. The data that has obtained will be processed using quantitative methods and qualitative methods. The results of the study with the development method that the author received from filling out the questionnaire included aspects of the evaluation of media validation which consisted of 21 indicators, and media validation had two elements of assessment namely aspects of design appearance and programming aspects, the total score of the two aspects of the evaluation gained a total of 83 estimates and the average an average rating of 3.95 is in a Good category. Details of media validation are two indicators from the display aspect score 3 (9.25%), and four indicators score 4 (19.04%), while from the programming aspect there are 14 indicators score 4 (66.67%) and one indicator score 5 (4, 76%). The questionnaire assessment in terms of learning material received a total score of 49, with an average rating of 4.08 in the Good category. Recorded in terms of learning that has 12 indicators get an assessment with the details seven signs to get a score of 4 (58.33%), three symbols get a score of 5 (25%), and two indicators get a score of 3 (16.67%). While in terms of learning design, 11 signs obtained a total score of 45 an average rating of 4.09 and included in the category of Very Good. The distribution of the assessment questionnaire on the validation of the learning design recorded two indicators score 3 (18.18%), six signs score 4 (54.54%), and 3 symbols score 5 (27.27%).